FIQH PERNIKAHAN WARIA; Telaah Harapan Pernikahan Waria dalam Buku Jangan Lepas Jilbabku Karya Shuniyya Ruhama Habiballah - Nur Kholis (Faculty of Sharia and Law UNISNU Jepara, 2014)
This paper aims to; 1) Knowing the form of transvestite marriage that Shuniyya Habiballah Ruhama expected as stated in the book Jangan Lepas Jilbabku; Catatan Harian Seorang Waria. 2) Knowing the provisions of fiqh about transvestites in regard with marital problems. There is a gap of understanding between Shuniyya and jurisprudence regarding the married couple. The Shuniyya's hope for transvestis marriage is based on the beliefs, thoughts and deepest awareness that he is